(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
High resolution aeromagnetic data combined with the geological settings of the study area were employed in delineating the structures that may host the gold mineral within the middle parts of Anka schist belts. These data were analysed, processed and interpreted using; reduction to magnetic equator (RTE), first and second vertical derivatives (FVD & SVD), geologic contact, analytic signal (AS), centre for exploration targeting (CET) and source parameter imaging (SPI) techniques. RTE technique was applied to prevent North-South signal in the data from dominating the results, due to the area falls under the low latitude. FVD and SVD maps shows major NE trend of the structures within study area. CET map revealed the regions with linear structures (lineament) which were trending South-Eastern regions of the study area. Geologic contact map has highlighted high density of structural contacts combined with junctions and intersections of different structures found within the area. AS map enhanced the variation in the magnetisation of the magnetic sources and also indicates the boundaries of anomaly texture. These techniques have revealed the regions that may host gold mineralisation potential areas to be; northern parts of Bukkuyum, Anka, Maru, Sakaba, Mariga, southern part of Wasagu/Danko. Most of the structures (lineaments) found within areas were associated with the vein of the mineralisation potential which plays important role in determine a gold mineral. Results from these techniques also correlated